Development of an Asthma Home-Visit Training Program for Community Health Workers and Their Supervisors in Washington State - Elkugia, Nuha; Crocker, Mary E.; Stout, James W.; Bolt, Kaylin; Weiner, Bryan J.; Kramer, C. Bradley (Frontiers in Public Health, 2021)
The community health worker (CHW) asthma home-visiting model developed by Public Health-Seattle & King County (PHSKC) is an evidence-based approach proven to improve health outcomes and quality of life. In addition, it has been shown to be an effective and culturally appropriate approach to helping people with asthma understand the environmental and behavioral causes of uncontrolled asthma, while acquiring the skills they need to control their asthma. This paper describes the development and implementation of training curricula for CHWs and supervisors in the asthma home visiting program. To facilitate dissemination, this program took advantage of the current healthcare landscape in Washington State resulting from CMS approval of the 1115 Medicaid Waiver project. Key aspects of the training program development included: (1) Engagement: forming a Community Advisory Board with multiple stakeholders to help prioritize training content; (2) Curriculum Development: building the training on evidence-based home-visit protocols previously developed at PHSKC; (3) Implementation of the training program; (4) Evaluation of the training; and (5) Adaptation of the training based on lessons learned. We describe key factors in the training program’s improvement including the use of a community-based participatory approach to engage stakeholders at multiple phases of the project and ensure regional adaption; combining in-person and online modules for delivery; and holding learning collaboratives for post-training and technical support. We also outline our training program evaluation plan and the planned evaluation of the home visit program which the trainees will deliver, both of which follow the RE-AIM framework. However, because the COVID-19 pandemic has curtailed training activities and prohibited the trainees from implementation of these CHW home visit practices, our evaluation is currently incomplete. Therefore, this case study provides insight into the adaptation of the training program, but not the delivery of the home visit program, the outcomes of which remain to be seen.